MANUFACTURING AND HYDRAULIC VARIATIONS IN TRICKLE IRRIGATION SYSTEM - Reddy, K.S.; Rajput, T.B.S. (Journal of Soil and Water Conservation, 2022)
systematic field evaluation of trickle irrigation system was carried out to study the manufacturing and hydraulic variations in the system. The selected operating pressures ranged from 50 KPa to 170 KPa. The co-efficient of manufacturing variation and hydraulic variations are found to be below 5% and he emitters were found to deliver discharge rates uniformly at an operating pressure of 100 KPa in the actual field. In the flat topography (Zero slope), the manufacturing variation was found decreasing and hydraulic variation was found so be increasing with respect to increasing operating pressure, when compared to actual field.